Nanomaterials and Coatings for Managing Antibiotic-Resistant Biofilms - Guillem Ferreres; Kristina Ivanova; Ivan Ivanov; Tzanko Tzanov (MDPI AG, 2023)
Biofilms are a global health concern responsible for 65 to 80% of the total number of acute and persistent nosocomial infections, which lead to prolonged hospitalization and a huge economic burden to the healthcare systems. Biofilms are organized assemblages of surface-bound cells, which are enclosed in a self-produced extracellular polymer matrix (EPM) of polysaccharides, nucleic acids, lipids, and proteins. The EPM holds the pathogens together and provides a functional environment, enabling adhesion to living and non-living surfaces, mechanical stability, next to enhanced tolerance to host immune responses and conventional antibiotics compared to free-floating cells. Furthermore, the close proximity of cells in biofilms facilitates the horizontal transfer of genes, which is responsible for the development of antibiotic resistance. Given the growing number and impact of resistant bacteria, there is an urgent need to design novel strategies in order to outsmart bacterial evolutionary mechanisms. Antibiotic-free approaches that attenuate virulence through interruption of quorum sensing, prevent adhesion via EPM degradation, or kill pathogens by novel mechanisms that are less likely to cause resistance have gained considerable attention in the war against biofilm infections. Thereby, nanoformulation offers significant advantages due to the enhanced antibacterial efficacy and better penetration into the biofilm compared to bulk therapeutics of the same composition. This review highlights the latest developments in the field of nanoformulated quorum-quenching actives, antiadhesives, and bactericides, and their use as colloid suspensions and coatings on medical devices to reduce the incidence of biofilm-related infections.